Sosialisasi Pencegahan Dan Penanganan Kekerasan Di Lingkungan Satuan Pendidikan (PPKSP) Di SMA N 27 Batam - Ukas; Khairina, Etika; Jamba, Padrisan; Zukriadi, Diki; Lebang, Andika Surya (PUAN INDONESIA, 2025)
Violence is a violation of human rights that cannot be tolerated. This is in line with the mandate of the 1945 Constitution that everyone has the right to protection from violence and the right to be free from torture or behavior that degrades human dignity. The public has increasingly highlighted violence in the Academic Environment with the increasing number of victims who dare to reveal these actions. Schools should be a safe place for people in them from the threat of sexual harassment and violence. The phenomenon of criminality must be eradicated immediately, one of which is by trying to prevent sexual harassment and violence, so there needs to be prevention efforts and strict legal sanctions in dealing with cases of sexual harassment and violence. The government has strictly regulated harassment and forms of violence through Permendikbud Number 46 of 2023 concerning the Prevention and Handling of Violence in the Education Unit Environment (PPKSP). One of the efforts to prevent sexual harassment and violence is through socialization through several activities such as webinars and social campaigns that are covered in Community Service activities. This community service aims to provide an overview and raise awareness of the importance of understanding and knowledge among the school community about preventing and handling harassment, violence, and sanctions for these actions.